Social factors that predict fear of academic success. Issue 2 (2nd April 2016) - Gore, Jonathan S.; Thomas, Jessica; Jones, Stevy; Mahoney, Lauren; Dukes, Kristina; Treadway, Jodi
Abstract : Fear of academic success is ultimately a fear of social exclusion. Therefore, various forms of social inclusion may alleviate this fear. Three studies tested the hypothesis that social inclusion variables negatively predict fear of success. In Study 1, middle and high school students ( n =  129) completed surveys of parental involvement, parental support, and fear of success. Only parental support negatively predicted fear of success. In Study 2, college students ( n  = 184) completed surveys of school connectedness, social isolation, and fear of success. Only school connectedness negatively predicted fear of success. In Study 3, college students from two universities ( n  = 605 total) completed surveys of family support, school connectedness, and fear of success. Both family support and school connectedness negatively predicted fear of success. To solve the problems of fear of success, school resources should focus on enhancing family support and school connectedness.